Aseptic Meningitis with Urinary Retention: A Case Report - Fotinie Ntziora; Aristidis Alevizopoulos; Kostas Konstantopoulos; Sofia Kanellopoulou; Dimitrios Bougas; Konstantinos Stravodimos (Case Reports in Medicine)
Introduction. Aseptic meningitis is serious inflammation of the meninges caused by agents including viruses, non-viral pathogens, non-infectious conditions and chemicals. Case Presentation. This study concerns the case of a 16-year-old healthy Greek female with persistent fever, mild headache and acute urinary retention, secondary to aseptic meningitis. Physical examination revealed no distinct signs of meningeal irritation. The urinary bladder was palpable, painless and over-distended. Serology carried out for common viruses was as follows: CMV IgG (−), CMV IgM (−), HSV IgG (−), HSV IgM (+), VZ IgG (+), VZ IgM (−), EBV IgG (−) and EBV IgM (+). During recovery in hospital, three trials of removing a urinary catheter were carried out; during the first two attempts the patient was unable to urinate and had a loss of bladder sensation. On the third attempt the patient had modest bladder perception but she left a post-voiding residual, and was instructed to perform bladder self-catheterization. Seven days after being discharged the patient underwent a full recovery. Conclusion. There are few reports concerning aseptic meningitis together with acute urinary retention. A number of these cases concern so-called “meningitis-retention syndrome,” which implies an underlying CNS mechanism, while others concerned an underlying peripheral nervous system mechanism.